EBV-positive post-transplant lymphoproliferative disorder presenting as primary diffuse large B-cell lymphoma of the central nervous system - Xu, Haoliang; Rewerska, Julia; Aardsma, Nathan; Slavin, Konstantin; Valyi-Nagy, Tibor; Ni, Hongyu (Folia Neuropathologica, 2017)
Primary central nervous system post-transplant lymphoproliferative disorder (PCNS-PTLD) is a rare complication with inferior survival outcomes in solid organ transplant patients. It represents approximately 7-15% of all PTLD patients. Because of the rarity of this disease, the diagnosis of PCNS-PTLD is often challenging, and the optimal therapy has not been established. We report a case of a renal transplant patient who initially presented with acute altered neurological function, an enhancing mass lesion of the brain on magnetic resonance imaging (MRI), and nonspecific reactive histopathological changes on brain biopsy. The lesion was self-limited and spontaneously resolved without medical treatment for PTLD. Six months later, surveillance MRI revealed recurrence of the brain lesion. The biopsy showed morphologic changes consistent with Epstein-Barr virus (EBV)-positive diffuse large B-cell lymphoma. The patient responded well to reduction of immunosuppression and treatment with a single-agent regimen of rituximab. This is an unusual case of PCNS-PTLD with an initial presentation resembling a self-limited reactive lesion.